Empowering MSMEs through Graphic Design to Improve Sales - Maulana, Yusril Ishaq; Rahmawati, Lilis; Nurmawati, Nurmawati; Brata, Diah Puji Nali (Bisma : Bimbingan Swadaya Masyarakat, 2023)
This article contains devotion as a form of development efforts and increased selling power during the Covid 19 pandemic MSMEs in Sugihwaras village. During a pandemic like this, MSME actors make the majority of the economic sector, especially MSME actors, experiencing a decrease in sales, so that the majority of MSMEs stagnate and even bankruptcy. This is what makes MSMEs change marketing strategies through digitalization. Digitalisai schemes utilize market places (intermediaries) and use social media as a marketing technique. In addition, digital MSMEs must be able to synergize with netizens in the marketing of products and services. Thus the digital MSME development scheme can be one of the alternatives to save business actors in the midst of the Covid-19 pandemic. Through graphic design and making marketing designs are expected to increase consumer appeal and add skills in the field of graphic design. In this article using the ABCD (Asset Based Community Development) method where we tried graphic design training as an effort to increase the selling power of MSMEs especially in our area of Sugihwaras village. The result of this devotion, MSME actors gain knowledge and design skills, which are used for their product promotion pamphlets, in addition, MSME participants can also use design skills for other things